Estudo químico de Eugenia calycina Cambess e avaliação das atividades antimicrobiana, antioxidante e inibidora de alfa-amilase - Sousa, Raquel Maria Ferreira de (2015)
The chemistry of natural products is highlighted in the search for alternative therapy against bacteria and the replacement of synthetic products by natural ones, such as natural antioxidants, which can be used as preservatives in foods and as digestive enzyme inhibitors. In this context, this study aimed to identify the chemical composition of the essential oil (EO) of Eugenia calycina, determine its antimicrobial activity against oral cavity bacteria, evaluate the antioxidant capacity and α-amylase inhibitory activity of the extracts of leaves, flowers and branches from this species and identify some compounds responsible for these activities. The EO chemical composition was determined by gas chromatography coupled to mass spectrometry (GC-MS). Oxygenated and non-oxygenated sesquiterpenes were identified. The major compounds were spathulenol (21.36%), bicyclogermacrene (19.30%) and β-caryophyllene (8.57%). The EO was fractionated and submitted to analysis of antimicrobial activity with oral cavity bacteria. The EO and fraction 1 (containing only non-oxigenated sesquiterpenes) showed strong antibacterial activity (minimum inhibitory concentration, MIC, of 100 μg mL-1) against Porphyromonas gingivalis and Prevotella nigrescens. Fractions 3 and 4 (containing oxygenated sesquiterpene) showed strong activity (MIC's between 50 and 200 μg mL-1) for most bacteria tested (except the Actinomyces naeslundii). The EO and its fractions presented low toxicity to HeLa cells. Extract of the leaves, flowers and branches presented high concentration of the total phenolic content and proanthocyanidins, what justifies the high antioxidant capacity (EC50<50 μg mL-1) determined by DPPH scavenging method and α-carotene /linoleic acid system. The extracts were fractionated by liquid-liquid partition. By differential pulse voltammetry analysis (DPV) it was found that the fractions (ethyl acetate and n-butanol) with stronger antioxidant activity exhibited a high amount of charge and thus high concentration of compounds with antioxidant capacity. The chemical prospecting, the UV/Vis spectrum analysis and the flavonoid content showed the presence of flavonoids of the flavonols type in the composition of leaves and flowers, whereas branches showed proanthocyanidin and flavan-3-ols. Ethyl acetate and n-butanol fraction showed high α-amylase inhibitory activity, and this fact is correlated to the high phenolic compounds content. The ethyl acetate fraction of the leaves was subjected to column chromatography in which flavonol rutin, isoquercitrin and quercitrin, and flavan-3-ol (-)-epicatechin were isolated and identified (by UV-Vis, NMR and ESI-MS/MS). These compounds showed high antioxidant capacity and α-amylase inhibitory activity, which are the responsibles for the activity observed in the extracts. Through dereplication analysis by liquid chromatography coupled to mass spectrometer (HPLC-ESI-MS/MS), it was possible to identify the presence of B2 and C1 procyanidins in the ethyl acetate fraction of the leaves. Furthermore, the ethyl acetate fraction of the flowers showed the same compounds isolated in the leaves, while the branches found to be only the presence of epicatechin, B2 and C1 procyanidins. The compounds isolated were quantified by HPLC. Leaves showed high concentration of quercitrin and epicatechin in the ethyl acetate fraction and rutin in the n-butanol fraction. The flowers exhibited high concentration of quercitrin and rutin in the ethyl acetate and n-butanol fractions. The branches showed high concentration of epicatechin in the ethyl acetate fraction. Thus, E. calycina is very promising to develop possible drugs and herbal medicines.